Promising roles of Zingiber officinale roscoe, Curcuma longa L., and Momordica charantia L. as immunity modulators against COVID-19: A bibliometric analysis - Sheikh Mohamed, Hassan Ibrahim; Zakaria, Nor Hafizah; Abdul Majid, Fadzilah Adibah; Zamzuri, Fatihah; Fadhlina, Anis; Hairani, Muhammad Afnan Shakir (Elsevier B.V, 2023)
Zingiber officinale, Curcuma longa, and Momordica charantia are medicinal plants that are commonly used in the form of herbal tea, which is formulated to strengthen the immune system, especially against COVID-19 infection. Excellent antioxidant, anti-inflammatory, and immunostimulatory properties have been reported for their bioactive compounds, which have been shown to aid in stimulating immune systems as well as lowering the risk of severe COVID-19 such as lung injury. Yet, no bibliometric study on the subject is available. Hence, the purpose of this study is to quantitatively examine the existing articles related to the therapeutic potential of these three herbs, as well as their mechanisms of action in combating the SARS-CoV-2 virus. A total of 121 papers were retrieved from Scopus database up to 14th March 2023. The bibliometric analysis was conducted using VOSviewer software. Based on the literature search, Z. officinale was the most researched plant. India appeared as the most prolific country, with the highest number of articles contributed by two authors from India (Rathi, R. and Gayatri Devi, R.). In terms of keywords, the plants were associated with immune modulation, management of symptoms, antioxidant, anti-inflammatory and antiviral activities. Several important bioactive compounds were responsible for these effects such as gingerol, paradol, shogaol, curcumin, calebin A, momordicoside, karaviloside and cucurbitadienol. These compounds were hypothesized to prevent and cure COVID-19 by regulating inflammatory response, downregulating oxidative stress and modulating immunostimulatory activity. This review paper therefore supports the potential of Z. officinale, C. longa, and M. charantia to be formulated as a herbal blend for treating and preventing COVID-19 infection.